The Meaning and Historical Value of Gorga in Batak Toba’s Traditional House - Peninna Simanjuntak; Martha Pardede (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This study aims to understand the historical value, meaning and function of the "Gorga" ornament in the Batak Toba traditional house which was reviewed with a Semiotic Study. The method used in this research is descriptive method. Descriptive method can be interpreted as a problem-solving procedure that is investigated by describing / describing the state of the object / research subject (a person, institution, community, etc.) at the present time based on the facts that appear as they are. The results of field research show that ornaments have a very influential relationship with the social life of the Batak Toba people, where these ornaments are used as guidelines to assess an action taken by one person against another or serve as material for living a harmonious life. This can be seen from the understanding that is revealed in the field where the meanings that appear are closely related to the actions that are often carried out by the community. The conclusion of this study is that Gorga or traditional sculptures which are usually found on the outer walls of houses and the front of traditional houses or also called ornaments that contain mystical elements that repel reinforcements and have philosophical values of Batak culture. The output of this research will be published in an international journal indexed by sinta.